Critical appraisal of oncological safety of stent as bridge to surgery in left-sided obstructing colon cancer; a systematic review and meta-analysis. (November 2018) - Amelung, Femke J.; Burghgraef, Thijs A.; Tanis, Pieter J.; van Hooft, Jeanin E.; ter Borg, Frank; Siersema, Peter D.; Bemelman, Willem A.; Consten, Esther C.J.
Highlights: Long-term oncologic outcomes seem similar when emergency surgery is compared to stent placement. Permanent stoma rate is lower when patients are initially treated with SEMS as bridge to surgery. Sensitivity analysis shows opposite outcomes, with a trend towards worse survival in the SEMS group when only RCTs are taken into account. Adequate experience with SEMS placement seems of importance for long-term oncologic outcomes. Abstract: This meta-analysis aims to determine the long-term oncological outcomes of SEMS as bridge to surgery (BTS) versus emergency surgery (ES). A systematic search without restrictions was conducted, and all studies comparing SEMS with ES reporting on long-term outcomes were included. Methodological quality was assessed using the appropriate tools. Twenty-one comparative studies were selected, reporting on 1919 patients. Meta-analysis showed no significant difference regarding three- and five-year overall survival (OR = 0·85 (0·68-1·08) and OR = 1·04 (0·68-1·57), respectively), disease-free survival (OR = 0·96 (0·73-1·26) and OR = 0·86 (0·54-1·36), respectively) and local recurrence rate (OR = 1·32 (0·78-2·23)). Permanent stomas were significantly lower in the SEMS group (OR 0·49 (0·32-0·74)). Sensitivity analysis on three-year survival showed opposite outcomes, with a trend towards worse survival in the SEMS group when only RCTs are taken into account. In conclusion, when in experienced hands, SEMS placement as BTS seems oncologically safe.